Native Plants: An Overview - Jeffrey G. Norcini (EDIS)
ENH-1046, an 8-page illustrated fact sheet by Jeffrey G. Norcini, describes the economics of native plant production, the legal definitions of native plants, key terms related to native plants, and issues faced by growers and consumers. Includes references. Published by the UF Department of Environmental Horticulture, December 2006.